ON DETERMINATION FEATURES OF ‘DOCUMENT’ CONCEPT FACULTATIVE PART - Vera V. Boguslavskaya; Igor V. Boguslavskiy (Advanced Engineering Research)
The definition features of the facultative part of the ‘document’ concept are considered. The signs of the commun ication media document are presented. A new statement of the problem on the branch definition of the document is given.